Wnt-dependent mechanism of the apical constriction of roof plate cells in developing mouse spinal cord - Shinozuka, Takuma; Okubo, Tadashi; Sasai, Noriaki; Takada, Shinji (Frontiers in Cell and Developmental Biology, 2025)
Apical constriction of epithelial cells usually occurs in a local portion of epithelial sheet, which results in bending of epithelial tissues. However, it is uncertain whether diffusible signal molecules, like Wnt, regulate such locally restricted events. Here, we show that Wnt ligands are required for apical constriction of Wnt1-expressing roof plate (RP) cells during development of the neural tube. Analysis of Wntless conditional knock-out (cKO) embryos, in which Wnt secretion from Wnt1-expressing roof plate cells is impaired, revealed that RP-derived Wnt ligands are required for phosphorylation of myosin light chain (MLC) and apical constriction of RP cells. Loss- or gain-of-function analysis of β-catenin reveals that this apical constriction is regulated in a β-catenin-dependent manner. Consistent with the timing of apical constriction, Wnt ligands accumulate on the apical side of RP cells. In embryos with Wnt1-expressing RP-specific defects in synthesis of heparan sulfate proteoglycan, apical accumulation of Wnt ligands and apical constriction are impaired. Therefore, we propose that specific accumulation of Wnt ligands on RP cells drives apical constriction of these cells.